Pengaruh Pemberian Ekstrak Buah Alpukat (Persea americana mill) terhadap Kadar Trigliserida Darah Pada Tikus (Rattus norvegicus) Putih Jantan Obesitas - Sirait, Dewi Suryaningsih; Sihombing, Jenny Ria; Sipayung, Novreka (Universitas HKBP Nommensen, 2022)
Background: Triglycerides are a type of fat the blood obtained from the breakdown of food. The body uses triglycerides as the main element in the formation of energy and various metabolic processes and the formation of cell membranes to perform other cell functions.Objective: The study aims to determine whether there is the effect of giving the extract of avocado (Persea americana mill) on triglyceride blood levels in obese male white rats and to determine triglyceride levels before and after administration of the extract of avocado.Methods: The design of this study used precilincal experimental design with pre-post design (one-group pretestpostest). The sample of this study was 10 samples of obese male white rats and met the inclusion and exclusion criteria. Sampling was out by taking blood from the tail of the obese male white rats. Data analysis in the study was carried out by bivariate method, normality test using the Shapiro-Wilk test.Results: From the analysis, the data results showed the mean of control rats before and after treatment of 165.6 mg/dL and 126.4 mg/dL with SD 23.50 and 28.02. The mean of treatment rats before and after 172.2 mg/dL and 124.0 mg/dL with SD 41.08 and 38.26 and obtained p value <0.001.Conclusion: There is an effect of giving the extract of avocado to th triglyceride levels in obese male white rats